All Our Data Will Be Health Data One Day: The Need for Universal Data Protection and Comprehensive Consent - Schneble, Christophe Olivier; Elger, Bernice Simone; Shaw, David Martin (JMIR Publications, 2020)
Tremendous growth in the types of data that are collected and their interlinkage are enabling more predictions of individuals' behavior, health status, and diseases. Legislation in many countries treats health-related data as a special sensitive kind of data. Today's massive linkage of data, however, could transform "nonhealth" data into sensitive health data. In this paper, we argue that the notion of health data should be broadened and should also take into account past and future health data and indirect, inferred, and invisible health data. We also lay out the ethical and legal implications of our model.